A case of factitious disorder presenting with hematohidrosis: a rare case report (Bangladesh Journal of Psychiatry, 2020)
Factitious disorder is described as the patient’s intention to produce fake symptoms to play a sick role and gain medical attention.1 The symptoms could be physical, psychological or mixed. The wide spectrum of symptoms makes the diagnosis and management challenging. This is a case report of a 17 year old girl who was referred to us with history of recurrent bleeding from left side of her forehead. Detailed hematological investigations revealed no abnormal causes of bleeding but on clinical examination, we found multiple scar marks on the affected site. The history was suggestive of hematohidrosis but the patient had scar marks on the affected area which indicated that the bleeding was self-inflicted. This was the most important diagnostic and differentiating point in this patient. Pharmacotherapy and psychotherapy were followed by complete remission.Bang J Psychiatry June 2018; 32(1): 19-21